Industrialización del cuy - Cárdenas Araque, Jefferson Josué (2017)
The general research project "INDUSTRIALIZATION OF GUINEA PIG" and the specific topic "DELI BARBECUY"; (Cavia porcellus) and take advantage of this species: prolific, gentle, easy to adapt to the environment, with a meat of high nutritional value and Healthy, with the purpose of producing canned and vacuum packed in different types of sauces. In the canton of Salcedo in the province of Cotopaxi there is a production estimated 35,000 guinea pigs that have not been commercialized in this type of presentation, if not in a traditional way helping in this way to generate an innovative way to market the guinea pig, increasing Its added value, the raw material was acquired from the hatchery located in the San Miguel de Salcedo Parish of the Engineer Edison Altamirano the same one that has an adequate infrastructure for the breeding and commercialization of guinea pigs in foot and dress. To guarantee the safety of the canning and the vacuum packing was sterilized in a steam autoclave at 120 ° C for 30 minutes, discarding the presence of any type of microorganism demonstrated in the physical chemical and microbiological analyzes of the best treatment that was carried out In an accredited quality assurance and analysis laboratory.